Pemberian Kompos Tandan Kosong Kelapa Sawit dan Zat Pengatur Tumbuh Alami terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guinensis Jacq.) di Pembibitan Utama Menggunakan Medium Subsoil Ultisol - Amri, Al Ikhsan (Jurnal Agro Teknologi Tropika, 2014)
This research aim was to study the effects of applying oil palm empty fruit bunches compost and natural growthregulator substances on growth palm oil ( Elaeis guineensis Jacq.). This research was conducted in screen house ofAgricultural Faculty, University of Riau, from December 2012-April 2013. Subsoil ultisol was taken from Kulim RegionPekanbaru. Soil chemical properties of ultisol material was analyzed at Soil Laboratory of Soil Research Bogor. Thisresearch used a split plot design as the main plot was natural growth regulator substances and subplot was oil palmempty fruit bunches compost consists of 3 treatments in the main plot and 4 in the subplot. The treatments in the mainplot: Z0 = without natural growth regulator, Z1 = natural growth regulator substances using banana corm, Z2 =natural growth regulator subtances using bamboo shoots. The treatments in subplot: T0 = without oil palm empty fruitbunches compost, T1 = 20 tons per ha of oil palm empty fruit bunches of compos, T2 = 30 tons per ha of oil palm emptyfruit bunches of compos, T3 = 40 ton per ha of oil palm empty fruit bunches of compos. The result showed that applicationof oil palm empty fruit bunches compost 20 tons per ha, without or with natural growth regulator subtances increasedplant height, number of leaves and diameter hump.